2005
DOI: 10.1002/cncr.20798
|View full text |Cite
|
Sign up to set email alerts
|

Microsatellite distribution and indication for locoregional therapy in small hepatocellular carcinoma

Abstract: BACKGROUND Intrahepatic disease recurrence is observed frequently after locoregional therapies for patients with hepatocellular carcinoma (HCC). However, the indication for locoregional therapy is still unclear. To clarify the indication for locoregional therapy for small HCC tumors, the authors measured the distance of microsatellites from the main tumor and analyzed the relation between this distance and clinicopathologic factors. METHODS The authors retrospectively analyzed 100 patients with small HCC tumor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
115
3
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(119 citation statements)
references
References 33 publications
0
115
3
1
Order By: Relevance
“…By the same rule, tumor satellite distance (TSD), which reflects the sprea-ding ability of tumor satellites and is regarded as a prognosticator in hepatocellular carcinoma initially, is defined as the distance from the main tumor to the most distant tumor satellite [85]. It has been demonstrated that TSD can also serve as a significant prognosticator of SCC in the oral cavity.…”
Section: Tumor Satellites and Tumor Satellite Distancementioning
confidence: 99%
“…By the same rule, tumor satellite distance (TSD), which reflects the sprea-ding ability of tumor satellites and is regarded as a prognosticator in hepatocellular carcinoma initially, is defined as the distance from the main tumor to the most distant tumor satellite [85]. It has been demonstrated that TSD can also serve as a significant prognosticator of SCC in the oral cavity.…”
Section: Tumor Satellites and Tumor Satellite Distancementioning
confidence: 99%
“…The likelihood of local progression increases with tumor size as a result of satellite nodules (8), which is why a 5-mm minimum ablation margin is recommended by several studies (9,10). However, some of these studies (9,11,12) used a rigid registration that is not optimal for the liver because of significant deformations by respiratory movements and the ablation zone (13).…”
mentioning
confidence: 99%
“…In larger tumors, other prognostic factors may mask the benefit from AR, while in very early HCC (< 2 cm), the risk for tumor spread along portal pedicles is limited. Pathology studies confirmed that microsatellites and thrombosis are extremely rare for very early HCC [34]. Second, superficial HCC are treated by non-AR even in centers regularly performing AR.…”
Section: Resultsmentioning
confidence: 98%
“…In the very early and early stage HCC, several randomized controlled trials demonstrated the superiority of RFA versus PEI, with complete response rates of 95–96% for RFA vs. 82–86% for PEI, 2-year local recurrence rates of 2–18 vs. 11–33%, and 3-year survival rates of 74–81 vs. 55–73% [72, 73]. This superiority has been mostly attributed to the capability of RFA to ablate a rim of perilesional non-tumoral tissue where microsatellite nodules are frequently located [34]. Nowadays, PEI has a very limited role for the treatment of tiny (≤10 mm) HCC, mostly located in anatomical areas at risk for ablation (adjacent to gallbladder, main bile ducts, or bowel loops).…”
Section: Resultsmentioning
confidence: 99%